Voyager from Xanadu : Rabban Sauma and the first journey from China to the West - Rossabi, Morris (University of California Press, 2010)
In Voyager from Xanadu, a distinguished historian tells the little-known story of the life and travels of the first person from China ever to reach Europe. Portraying one of the most remarkable early encounters between East and West, Morris Rossabi also brings to life the intriguing and turbulent era of the Mongol Empire and the last Crusades. Toward the end of the thirteenth century, at about the time Marco Polo arrived in China, a Christian monk, Rabban Sauma, left it, embarking on a journey that would prove more momentous than he could have dreamed. What began as a religious pilgrimage to the Middle East (supported by the Mongol Emperor, Khubilai Khan) ultimately became an extraordinary diplomatic mission. After several years' eventful stay in Persia, Sauma was dispatched to Europe by Persia's Mongol ruler, the Ilkhan. The monk's task: to persuade the Pope and the Kings of France and England to ally with the Ilkhan and launch a Crusade against their common enemy, the Muslim dynasty that controlled the Holy Land. The mission was a striking early instance of geopolitics on a modern scale. Voyager from Xanadu vividly conjures up the places Sauma visited as he crossed two continents, meeting with monarchs and prelates and seeing everything from a battle to a volcanic eruption to countless grisly relics of long-dead saints. It provides a clear and penetrating analysis of the volatile international situation of the era and its impact on Sauma's embassy. And, of course, Voyager from Xanadu traces the life of an exceptional man, from his comfortable youth, through his unique adventures, to his death far from the land of his birth.